Automated Grading System with Student Performance Analytics - Brittaney E. Bato; Jake R. Pomperada (Philippine Social Science Journal, 2025)
This study developed the Student Performance Analytics and Grading Automation System to modernize traditional grading processes at Colegio de Santa Rita de San Carlos Inc. Built using Laravel and modern web technologies, the system automates grading and provides real-time performance analytics while ensuring seamless online and offline functionality. Key features include role-based access control, data encryption, and optimization for low-spec hardware to ensure accessibility. User evaluations rated the system’s performance as "Excellent," highlighting its intuitive interface, reliability, and security. By streamlining administrative tasks and offering predictive insights, the platform enhances data-driven decision-making and aligns with the institution's digital transformation goals. Future development will focus on advanced predictive modeling, regulatory compliance, and scalable adoption across broader educational networks.